Opioid peptide and alpha-adrenoceptor pathways in the regulation of the pituitary-adrenal axis in man. - Delitala, G; Trainer, P; Oliva, O; Fanciulli, G; Grossman, A (1994)
Opioid peptides are well established as potent inhibitors of the pituitary-adrenal axis, while alpha 1-adrenoceptor drugs have recently been shown to stimulate this axis: both classes of agents appear to work principally above the level of the pituitary, most probable directly on the hypothalamus. There is also evidence that these drugs interact in their control of pituitary-adrenal function, although the specific hypothalamic releasing hormone involved has remained unclear. We have therefore carried out a study into the interaction of methoxamine, an alpha 1-adrenoceptor agonist and naloxone, an opioid antagonist, together with human corticotrophin-releasing hormone (CRH), in a group of healthy volunteers in order to establish the mode of action of these drugs. The following drugs were administered to a group of seven healthy male subjects in a randomized double-blind manner: methoxamine (6 micrograms/kg per min over 3 h); naloxone (10 mg bolus); human CRH (100 micrograms bolus); methoxamine plus CRH; naloxone plus CRH; methoxamine plus naloxone; saline (control). Plasma ACTH and serum cortisol were measured at intervals in each subject, and blood pressure and pulse rate recorded with each sample. Both CRH and naloxone produce a marked rise in ACTH and cortisol, peaking at approximately 45 min after infusion. In combination, the drugs produced a peak response in plasma ACTH at the same time, but its magnitude was greater than that after either drug alone. Methoxamine produced a rise in plasma ACTH which was maximal at approximately 75 min, as well as a peak rise in serum cortisol at 120 min.(ABSTRACT TRUNCATED AT 250 WORDS)